Problematika Pendidikan Islam di Indonesia - Marjuni Marjuni (Al-Hikmah Journal for Religious Studies, 2011)
The first verse was sent by Allah swt. to the Prophet Muhammad saw. is the command to learning and teaching. From this fact, it can be concluded that Islam is very concerned with teaching and learning (in the context of studying). Thus, Islam obligates its followers to learn and teach. Moreover, in the Qur’an it can be found many sentences or verses which suggest Moslems to use their intelectual capacity, such as; ya'qilun (to think), yatafakkarun (to observe), yubsirun (to delight), yasma'un (to hear) and so on. Globalization in education could be considered as one of education challenge to recent years, and nobody can avoid it. Indonesia as a nation should face this challenge and put strategies to get chances from global interactions and not only to be consuments of international market but to be a player from international communities